The Evaluation of Malpraxis Cases which Had Been Negotiated by the General Assembly of the Council of Forensic Medicine for the Contradictory Opinions Between the Specialty Commitee SC of Council of Forensic Medicine and Supreme Commitee on Health - Güzel, Sadullah; Yavuz, Mehmet Sunay; Aşırdizer, Mahmut (The Bulletin of Legal Medicine, 2002)
Diseases, disablements and deaths which had been claimed to be caused by faulty behaviours of medical doctor and other health personnels or the health instutions have been increasingly coming to the agenda of courts recently. For these, SCH and CFM are charged to the expertise according to the tenors of the laws. Courts consult to SC of CFM on civil lawsuit cases of malpraxis to determine whether there is any fault of medical doctor and/or other health personnel and if there is any fault, to determine the degree of this fault for each without taking any opinion of SCH, but in cases of criminal suits the opinion of SCH should be prior. Sometimes, contradictionary opinions arise between the reports of these two instutions and in these situations, courts consult with GACFM. In this study, we examined reports of the SC of CFM, GACFM and SCH for 29 cases, the reports of SCH had been presented in 19 cases and hadn’t been presented for 10 cases. The degree of fault for medical doctor, assistant health personnel and hospital were asked. The data were presented after classification. The great discordance between the results of decision of SCH and of the SC of CFM or GACFM were significant. The primary reason for the defined discordance was interpreted as being the construction of SCH, SC of CFM and GACFM. Key words: Malpraxis, Forensic Medicine, Courts.